Best Darn Statistics Workbook Ever - Hauselt, William J.; Mugno, Raymond (Kendall Hunt Publishing, 2021)
Keywords: dept.mat; dept.psy

Morpholino-mediated knockdown of the brain mineralocorticoid receptor affects glucocorticoid signaling and neuroplasticity in wild ocellated wrasse (Symphodus ocellatus) - Nugent, Bridget M.; Stiver, Kelly A.; Han, Jiawei; Kindsvater, Holly K.; Marsh-Rollo, Susan E.; Hofmann, Hans A.; Alonzo, Suzanne H. (BioRxiv, 2021)
Keywords: dept.psy; ⛔ No DOI found

Ejaculate allocation and sperm characteristics differ among alternative male types in a species of fish with cooperation and competition among unrelated males. - Alonzo, Suzanne H.; Stiver, Kelly A.; Kindsvater, Holly K.; Marsh-Rollo, Susan E.; Nugent, Bridget; Kazancıoğlu, Erem (Cells, 2021)
Sexual selection arising from sperm competition has driven the evolution of immense variation in ejaculate allocation and sperm characteristics not only among species, but also among males within a species. One question that has received little attention is how cooperation among males affects these patterns. Here we ask how male alternative reproductive types differ in testes size, ejaculate production, and sperm morphology in the ocellated wrasse, a marine fish in which unrelated males cooperate and compete during reproduction. Nesting males build nests, court females and provide care. Sneaker males only “sneak” spawn, while satellite males sneak, but also help by chasing away sneakers. We found that satellite males have larger absolute testes than either sneakers or nesting males, despite their cooperative role. Nesting males invested relatively less in testes than either sneakers or satellites. Though sneakers produced smaller ejaculates than either satellite or nesting males, we found no difference among male types in either sperm cell concentration or sperm number, implying sneakers may produce less seminal fluid. Sperm tail length did not differ significantly among male types, but sneaker sperm cells had significantly larger heads than either satellite or nesting male sperm, consistent with past research showing sneakers produce slower sperm. Our results highlight that social interactions among males can influence sperm and ejaculate production. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Animals; Fishes; Male; Reproduction; Spermatozoa; Testis; adult; animal; article; controlled study; court; dept.psy; female; fish; human cell; male; metabolism; nesting; nonhuman; peer-reviewed; phenotypic plasticity; reproduction; seminal plasma; sexual selection; social interaction; sperm competition; sperm count; spermatozoon; spermatozoon tail; testis

Positive psychology: Exploring a mindful approach to online learning in higher education - DeLucia, Christine A. (Emerging Realities and the Future of Technology in the Classroom, 2021)
Keywords: dept.psy

Audiovisual speech perception in children with autism spectrum disorders: Evidence from visual phonemic restoration. - Irwin, Julia; Avery, Trey; Kleinman, Daniel; Landi, Nicole (Journal of autism and developmental disorders, 2021)
Children with autism spectrum disorders have been reported to be less influenced by a speaker’s face during speech perception than those with typically development. To more closely examine these reported differences, a novel visual phonemic restoration paradigm was used to assess neural signatures (event-related potentials [ERPs]) of audiovisual processing in typically developing children and in children with autism spectrum disorder. Video of a speaker saying the syllable /ba/ was paired with (1) a synthesized /ba/ or (2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant were substantially weakened, thereby sounding more like /a/. The auditory stimuli are easily discriminable; however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. Only children with ASD showed a large /ba/-/a/ discrimination response in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.
Keywords: Auditory Perception; Autism Spectrum Disorder; Child; Cues; Evoked Potentials; Humans; Speech; Speech Perception; Visual Perception; association; autism; child; dept.psy; evoked response; hearing; human; peer-reviewed; speech; speech perception; vision

The offspring of alcohol-exposed sires exhibit heightened ethanol intake and behavioral alterations in the elevated plus maze. - Koabel, Jennifer; McNivens, Meghan; McKee, Paul; Pautassi, Ricardo; Bordner, Kelly; Nizhnikov, Michael (Alcohol (Fayetteville, N.Y.), 2021)
Research suggests that addictive traits are indeed heritable, but very few preclinical studies have explored transgenerational effects of paternal alcohol exposure. The present study addressed this gap in knowledge. We explored whether offspring of ethanol-exposed sires would be more likely to accept ethanol than descendants of water-exposed and control sires. We also investigated whether the second generation of ethanol-exposed descendants would accept ethanol more than controls and were more or less likely to experience anxiety-like behavior in behavioral assessments. We exposed male rats to repeated binge doses of alcohol (4 g/kg/day across 8 days), water, or left them untreated and mated them with untreated females. We then bred the offspring of these rats to test transgenerational effects of paternal alcohol exposure. We tested 14-day-old offspring from the first and second filial generation for their acceptance of ethanol and water, and measured anxiety-like behavior in 38-day-old, second-generation offspring using an elevated plus maze. The results indicate that offspring of ethanol-exposed sires increase ethanol acceptance in the first generation compared to untreated controls, whereas in the second-generation increased ethanol acceptance vs. these controls is seen in descendants of both ethanol- and vehicle-treated sires. At adolescence, the second generation of rats derived from alcohol-exposed sires exhibited significantly more time spent in the open arms and significantly more arm entries than any other group. The present study suggests that parental ethanol exposure is associated with lingering effects in the infant and adolescent offspring. The second filial generation was also found to be affected, albeit similarly by grandparental ethanol exposure or by the stress of the vehicle administration. Copyright © 2021 Elsevier Inc. All rights reserved.
Keywords: Addictive; Alcohol Drinking; Animals; Anxiety; Article; Behavior; Elevated Plus Maze Test; Ethanol; Male; Maze Learning; Rats; Sprague Dawley rat; addiction; adolescence; adolescent; adult; alcohol; alcohol consumption; animal; animal experiment; animal model; anxiety; behavior disorder; binge drinking; breeding; concentration (parameter); controlled study; dept.psy; drinking behavior; elevated plus maze test; experience; exposure; female; grandparent; inhibitory control; male; maze test; newborn; nonhuman; paternal exposure; peer-reviewed; progeny; rat; sire; vertical transmission; water

Measurement of Motivation States for Physical Activity and Sedentary Behavior: Development and Validation of the CRAVE Scale. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Fogelman, Nia; Gilson, Todd A; Stanforth, Philip R; Divin, Amanda L; Bartholomew, John B; Filgueiras, Alberto; McKee, Paul C; Ash, Garrett I; Ciccolo, Joseph T; Brotnow Decker, Line; et al. (Frontiers in psychology, 2021)
Physical activity, and likely the motivation for it, varies throughout the day. The aim of this investigation was to create a short assessment (CRAVE: Cravings for Rest and Volitional Energy Expenditure) to measure motivation states (wants, desires, urges) for physical activity and sedentary behaviors. Five studies were conducted to develop and evaluate the construct validity and reliability of the scale, with 1,035 participants completing the scale a total of 1,697 times. In Study 1, 402 university students completed a questionnaire inquiring about the want or desire to perform behaviors "at the present moment (right now). " Items related to physical activity (e.g., "move my body") and sedentary behaviors (e.g., "do nothing active"). An exploratory structural equation model (ESEM) revealed that 10 items should be retained, loading onto two factors (5 each for Move and Rest). In Study 2, an independent sample (n = 444) confirmed these results and found that Move and Rest desires were associated with stage-of-change for exercise behavior. In Study 3, 127 community-residing participants completed the CRAVE at 6-month intervals over two years- two times each session. Across-session interclass correlations (ICC) for Move (ICC = 0.72-0.95) and Rest (ICC = 0.69-0.88) were higher than when they were measured across 24-months (Move: ICC = 0.53; Rest: ICC = 0.49), indicating wants/desires have state-like qualities. In Study 4, a maximal treadmill test was completed by 21 university students. The CRAVE was completed immediately pre and post. Move desires decreased 26% and Rest increased 74%. Changes in Move and Rest desires were moderately associated with changes in perceived physical fatigue and energy. In Study 5, 41 university students sat quietly during a 50-min lecture. They completed the CRAVE at 3 time points. Move increased 19.6% and Rest decreased 16.7%. Small correlations were detected between move and both perceived energy and tiredness, but not calmness or tension. In conclusion, the CRAVE scale has good psychometric properties. These data also support tenets of the WANT model of motivation states for movement and rest (Stults-Kolehmainen et al., 2020a). Future studies need to explore how desires to move/rest relate to dynamic changes in physical activity and sedentarism. Copyright © 2021 Stults-Kolehmainen, Blacutt, Fogelman, Gilson, Stanforth, Divin, Bartholomew, Filgueiras, McKee, Ash, Ciccolo, Brotnow Decker, Williamson and Sinha.
Keywords: dept.psy; peer-reviewed

Prediction of ethanol self-administration in pre-weanling, adolescent, and young adult rats. - Soledad Fernandez, Macarena; Edward Nizhnikov, Michael; Garcia Virgolini, Rodrigo; Marcos Pautassi, Ricardo (Developmental Psychobiology, 2021)
Alcohol (ethanol) use is almost normative by late adolescence, in most western countries. It is important to identify factors that distinguish those who progress from alcohol initiation to sustained use of the drug, from those that keep a controlled pattern of drinking. The factors precipitating this transition may change across development. This study analyzed associations between behavioral endophenotypes and ethanol intake at three developmental periods. Exp. 1 measured ethanol drinking at postnatal day 18, via an intraoral infusion procedure, in male or female pre-weanling rats screened for anxiety response in the light-dark box test and for distance traveled in a novel open field. Exp. 2 measured, in juvenile/adolescent or young adult rats, the association between shelter seeking, exploratory/risk-taking behaviors, anxiety or hedonic responses, and ethanol intake. Ethanol intake in pre-weanlings was explained by distance traveled in a novel environment, whereas anxiety responses, measured in the multivariate concentric square field apparatus (MSCF), selectively predicted ethanol intake at adolescence, but not at adulthood. Those juvenile/adolescents with lower mean duration of visit to areas of the MSCF that evoke anxiogenic responses exhibited heightened ethanol intake. These findings suggest that the association between anxiety and ethanol intake may be specifically relevant during adolescence. © 2020 Wiley Periodicals LLC
Keywords: Alcohol Drinking; Animals; Anxiety; Ethanol; Female; Male; Rats; Self Administration; Wistar; Wistar rat; adolescents; alcohol; animal; anxiety; dept.psy; drinking behavior; drug self administration; ethanol intake; female; male; peer-reviewed; pre-weanling rat; rat

Child and Adolescent Development: A Social Justice Approach - Anthis, Kristine (Cognella, 2021)
Child and Adolescent Development: A Social Justice Approach features portraits of development at each stage interwoven with the findings of developmental science research on how inequitable resources and opportunities, which are influenced by social, economic, and political factors, can impact development. The text also presents findings on how such data can be used to reduce inequities for children and their families, thereby optimizing development and allowing individuals to reach their full potential no matter who they are. The text begins with a chapter that briefly describes the stages, domains, and patterns of child and adolescent development, as well as traditional and contemporary theories. Subsequent chapters provide insight into the research methods of developmental science and explain how epigenetic influences affect development. The book then progresses chronologically, discussing the physical, cognitive, and emotional changes that occur within each stage, guiding readers through a tapestry of development from conception through adolescence. Throughout, Pan & Zoom sections supply both big-picture and microscopic understandings of development, Tech & Media asides highlight the influences that technology and media can have on child and adolescent development, and Mentor Minutes provide readers with practical wisdom through interviews with diverse professionals working in the field. Featuring a timely and much-needed perspective on development, Child and Adolescent Development is an ideal resource for courses in psychology, education, counseling, human services, and social work.
Keywords: Child development; Youth development; SCSU Faculty Scholar Award; award_winner; dept.psy